Effects of local vibration combined with extracorporeal shock wave therapy in plantar fasciitis: a randomized controlled trial - HyoJeong On; JongEun Yim (Medical Journals Sweden, 2023)
Objective:To compare the effects of local vibration combined with extracorporeal shock wave therapy and extracorporeal shock wave therapy alone for plantar fasciitis. Methods: A randomized controlled trial including 34 participants with a mean age of 37.5 years. Participants were randomly allocated to a group treated with extracorporeal shock wave therapy combined with local vibration (ESWT-LV group) or a group treated with extracorporeal shock wave therapy alone (ESWT-alone group). All participants in each group underwent 2 treatment sessions weekly for 5 weeks. Thickness of the plantar fascia, plantar pain, and foot function were measured using ultrasonography, numerical rating scale for pain, and Foot Function Index, respectively, at baseline and at the end of the 5-week intervention. Results: Significant improvements were measured in both groups in the thickness of the plantar fascia, numerical rating scale, and Foot Function Index values (p < 0.05). In addition, the thickness of the plantar fascia and pain was significantly more decreased in the ESWT-LV group than in the ESWT-alone group (p < 0.05). However, the differences between groups in Foot Function Index values were not significant (p > 0.05). Conclusion: Local vibration combined with extracorporeal shock wave therapy is an effective treatment for chronic plantar fasciitis.